Medicinal Significance of Ornamental Plants in Human Welfare from Akola District (M.S.) India - M.R., Rothe S. P.*, Bokhad M. N.; Kakpure (Journal of Experimental Sciences, 2011)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; background: white; padding-bottom: 0in; border-left: medium none; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> The present papers deals with the study of 35 ornamental plants planted in the gardens or as avenue tree, along with some cultivated plants, with their medicinal significance. Some valuable information was collected from medicine mens, labors and villagers by taking an oral interview.